Sub-15nm silicon lines fabrication via PS-b-PDMS block copolymer lithography - MORRIS, MICHAEL (Hindawi Publishing Corp., 2013)
This paper describes the fabrication of nanodimensioned silicon structures on silicon wafers from thin films of a poly(styrene)-block-poly(dimethylsiloxane) (PS-b-PDMS) block copolymer (BCP) precursor self-assembling into cylindrical morphology in the bulk. The structure alignment of the PS-b-PDMS (33 k–17 k) was conditioned by applying solvent and solvothermal annealing techniques. BCP nanopatterns formed after the annealing process have been confirmed by scanning electron microscope (SEM) after removal of upper PDMS wetting layer by plasma etching. Silicon nanostructures were obtained by subsequent plasma etching to the underlying substrate by an anisotropic dry etching process. SEM images reveal the formation of silicon nanostructures, notably of sub-15 nm dimensions.
PUBLISHED
Keywords: Polymers